ASEAN Mechanism for Human Security Problems in Southeast Asia: What's Wrong? - Natalia Yeti Puspita (Faculty of Law, Universitas Jenderal Soedirman, 2019)
Since the flow of goods and services begins to cross national borders, threats to human security do not originate solely from war. The era of traditional security has begun to shift towards non-traditional security or human security. In this concept, threats to security are directed directly at humans such as natural disasters, epidemics, drugs and human trafficking, and terrorism. Southeast Asia is the region most vulnerable to natural disasters. Relations between countries in this region are under the auspices of ASEAN. ASEAN Way is an ASEAN mechanism based on the principle of state sovereignty and non-intervention. ASEAN Way and Human Security are two different concepts. The ASEAN mechanism cannot be applied absolutely to overcome natural disasters that are massive, cross-border and occur in areas of armed conflict in Southeast Asia. In this case, it is necessary to broaden understanding of the nature of the principle of state sovereignty and non-intervention.Keywords: ASEAN Mechanism, Human Security, Southeast Asia